A hybrid de-noising method for mammogram images - Rashid Mehmood Gondal; Saima Anwar Lashari; Murtaja Ali Saare; Sari Ali Sari (Institute of Advanced Engineering and Science, 2021)
In general, mammogram images contaminated with noise which directly affect images quality. Several methods have been proposed to de-noise these images, however, there is always a risk of losing valuable information. In order to overcome the loss of information, the present study proposed a hybrid denoising method for mammogram images. The proposed hybrid method works in two steps: Firstly, preprocessing with mathematical morphology was applied for image enhancement. Secondly, global unsymmetrical trimmed median filter (GUTM) is applied to de-noise image. Experimental results prove that proposed method work well for mammogram images. Hence, the study provided an alternative method for denoising mammogram images.